OS 17-08 OBESITY, CARDIORESPIRATORY FITNESS AND THE RISK OF INCIDENT HYPERTENSION IN MEN. (September 2016) - Jae, Sae Young; Yoon, Eun Sun; Kim, Hyun Jeong; Choi, Yoon-Ho; Fernhall, Bo; Franklin, Barry
Abstract : Objective: Both obesity and cardiorespiratory fitness (CRF) are associated with increased risk of incident hypertension, but the combined association between obesity and CRF to predict incident hypertension remain unclear. We investigated the independent and combined associations of obesity and CRF with the risk of developing hypertension in men. Design and Method: Participants included 3770 apparently healthy men who initially presented without baseline evidence of hypertension, cardiovascular disease and diabetes. Per Asian criteria, obesity was defined as body mass index (BMI) ≥ 25 kg/m 2 and CRF was directly measured by peak oxygen uptake (VO2peak ) and divided into unfit (lower tertile) and fit (middle and higher tertile) categories based on age-specific VO2peak percentiles. HTN was defined as SBP/diastolic blood pressure greater than 140/90 mmHg and/or diagnosed HTN by a physician at baseline and follow-up examinations. Results: During a median follow-up of 5 years, 369 (9.8%) men developed new hypertension. After adjusting for age, SBP, total cholesterol, HDL-C, LDL-C, triglycerides, uric acid, resting heart rate, glucose, white blood cell count, cigarette smoking and alcohol consumption, the relative risk (RR) and 95% confidence interval (CI) for incident hypertension was 1.49 (95% CI, 1.13–1.97) for obese vs. normal weight and 0.70 (95% CI, 0.54–0.92) for fit vs. unfit. These associations were still statistically significant after adjusting for potential confounders with VO2peak (1.43, 95% CI, 1.08–1.89 for obese vs. normal weight) or BMI (0.74, 95% CI, 0.57–0.97 for fit vs. unfit). In the joint analysis, obese-unfit men had 1.83 times (95% CI, 1.37–2.45) greater risk of incident hypertension, but this risk did not significantly increase in obese-fit men (1.27, 95% CI, 0.91–1.77) as compared with normal weight-fit men. Conclusions: These results suggest that both obesity and CRF predict the incidence of hypertension independent of potential confounders; however, CRF appears to attenuate the risk of developing hypertension in obese men.